Treatment of Dural Carotid-Cavernous Sinus Fistula Through the Superior Ophthalmic Vein - Gamze Uçan; Bülent Yazıcı; Bahattin Hakyemez; Sevil Türüdü (Türk Oftalmoloji Dergisi, 2011)
Pur po se: To present 3 patients who had a dural carotid-cavernous sinus fistula (CCF) and underwent cavernous sinus embolization through superior ophthalmic vein (SOV) approach. Ma te ri al and Met hod: Medical records of 3 patients with dural CCF who were treated through SOV approach were reviewed. Patient’s age, gender, ophthalmic and radiological findings, treatment results, postoperative complications and follow-up time were recorded. Surgical procedure was performed in the interventional radiology unit and using general anesthesia. Through an eyelid crease incision, the SOV was reached and cannulated. The cavernous sinus was embolized with metalic coils advanced through a microcatheter placed into this cannula. Re sults: All 3 patients (3 female, patient ages: 41, 68 and 71 years) had Barrow type D CCF. One patient had a bilateral CCF. All patients had a history of unsuccessful treatment with interventional transvenous routes. The embolization procedure via the SOV was successfully completed in 2 patients. In a patient with bilateral CCF, the SOV was thin and tortuous, and could not be cannulated. All ophthalmic symptoms were improved in 2 patients with a successful embolization, and did not recur during the follow-up periods of 24 and 22 months. In one of these, an ischemic cerebrovascular event and orbital hematoma developed after the embolization. These complications improved without leaving a permanent impairment. Dis cus si on: Cavernous sinus embolization can be performed through SOV approach, when it can not be done via the interventional transvenous routes. This procedure may not be successfully performed in some cases because of the anatomical features of the SOV. After the operation, complications such as orbital hemorrhage and cerebral ischemic attack may occur. (Turk J Ophthalmol 2011; 41: 325-9)